Historical biogeography of the Late Cretaceous vertebrates of India : Comparison of geophysical and paleontological data - Verma, Omkar (2016)
Fil: Verma, Omkar. Geology Discipline Group. School of Sciences. Indira Gandhi National Open University. New Delhi; India